Persepsi Tamu terhadap Kualitas Layanan, Produk, dan Kepuasan di Metro Rent Apartemen Kalibata - Suesilowati; Latif; Rosandi Ardi Noegraha; Handi Hanif Aditya (Bulletin of Community Engagement, 2024)
Developments in the tourism sector are becoming increasingly necessary for the management of lodgings that are being developed as destinations so that they can compete for the attractiveness of the hotel market. This tourism development sector has resulted in the development of the accommodation industry in Jakarta. In other words, interesting things are needed to attract consumer attention in the marketing of the apartment. However, with so much competition in this business, it is increasingly difficult to get consumers. This marketing aims to expand the network and provide satisfaction and good quality service to consumers so that this marketing activity is attractive to various producing institutions. This research is included in quantitative research with a descriptive research approach. The data sources used are primary and secondary data. The data measurement technique uses a Likert Scale, which is used to measure attitudes, opinions, and perceptions of a person or group of people about social phenomena. This is a reference for consumers in choosing apartment accommodation